RANCANG BANGUN SISTEM IDENTIFIKASI PENGGUNAAN MASKER MENGGUNAKAN ARDUINO - Khoirunnisa, Rahmia; Ridho, Muhammat Rasid (Computer Science and Industrial Engineering, 2021)
After the breakout of pandemic COVID-19, there’s a important requirement for protection methods, the maximum important is a face masks. The task's fundamental aim is to locate the presence of a face masks on human faces in real time. Teachable Machine is the software used for this object detection because it makes creating machine learning models fast and easy with the introduction of this Arduino Uno and p5.js primarily based masks reminder device for humans beings to care more about their health. This assignment consists of a digital camera that detects whether or not a person is sporting a face masks or not the use of facial features, after which adding a serial command to the facemask detection set of policies that instructs the Arduino to turn on or off LEDs primarily based mostly on the country of detection.